2020
DOI: 10.48550/arxiv.2009.01127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taking Reinhardt's Power Away

Abstract: We study the notion of non-trivial elementary embeddings j : V → V under the assumption that V satisfies ZFC without Power Set but with the Collection Scheme. We show that no such embedding can exist under the additional assumption that it is cofinal and either V crit(j ) is a set or that the Reflection Principle holds. We then study failures of instances of collection in symmetric submodels of class forcings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Note that Ziegler [24] uses the term set cofinality to denote our notion of cofinality. However, we will use the term cofinality to harmonize the terminology with that of Matthews [18]. 4.…”
Section: Large Set Axiomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that Ziegler [24] uses the term set cofinality to denote our notion of cofinality. However, we will use the term cofinality to harmonize the terminology with that of Matthews [18]. 4.…”
Section: Large Set Axiomsmentioning
confidence: 99%
“…Proof. Matthews [18] showed that ZFC − with the Reflection principle proves there is no elementary embedding j : V ≺ V which is cofinal. By Theorem 2.15, RRS implies the Reflection principle, so we have a contradiction.…”
Section: Hence By Lemma 411 [[φ]]mentioning
confidence: 99%
See 1 more Smart Citation